2000
DOI: 10.1074/jbc.m005796200
|View full text |Cite
|
Sign up to set email alerts
|

Studies with Substrate and Cofactor Analogues Provide Evidence for a Radical Mechanism in the Chorismate Synthase Reaction

Abstract: Chorismate synthase catalyzes the conversion of 5-enolpyruvylshikimate 3-phosphate (EPSP) to chorismate. The strict requirement for a reduced FMN cofactor and a trans-1,4-elimination are unusual. (6R)-6-Fluoro-EPSP was shown to be converted to chorismate stoichiometrically with enzyme-active sites in the presence of dithionite. This conversion was associated with the oxidation of FMN to give a stable flavin semiquinone. The IC 50 of the fluorinated substrate analogue was 0.5 and 250 M with the Escherichia coli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 33 publications
1
39
0
1
Order By: Relevance
“…The blue shift of the flavin fluorescence maximum at 525 nm and the occurrence of an additional peak at 450 nm also suggest a more hydrophobic environment upon binding of EPSP to the binary NcCS⅐FMN complex (6). The hypothesis has been put forward that the hydrophobicity of the FMN binding pocket renders the reduced flavin a better electron donor for its assumed role as a transient electron transfer agent to EPSP to initiate cleavage of the C-O bond (4,5). However, to date no flavin radical species has been observed spectroscopically during EPSP turnover.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The blue shift of the flavin fluorescence maximum at 525 nm and the occurrence of an additional peak at 450 nm also suggest a more hydrophobic environment upon binding of EPSP to the binary NcCS⅐FMN complex (6). The hypothesis has been put forward that the hydrophobicity of the FMN binding pocket renders the reduced flavin a better electron donor for its assumed role as a transient electron transfer agent to EPSP to initiate cleavage of the C-O bond (4,5). However, to date no flavin radical species has been observed spectroscopically during EPSP turnover.…”
Section: Discussionmentioning
confidence: 99%
“…Although the reaction does not involve a net change in redox state, the enzyme has an absolute requirement for reduced FMN that is not consumed during substrate turnover. The role of reduced FMN has been subject to intense mechanistic studies (reviewed in Macheroux et al (3)) that have led to a proposal of a mechanism involving radical chemistry (4,5). Another issue revolving around the requirement for reduced flavin concerns the generation of the reduced cofactor and its sequestration by chorismate synthase.…”
mentioning
confidence: 99%
“…The reaction was terminated by the addition of 200 l acetonitrile to the mixture, and the mixture was centrifuged, filtered, diluted with acetonitrile-10 mM ammonium acetate (1:1), and then introduced into the mass spectrometer in the negative-ion mode at 5 l/min. For 18 O incorporation experiments, the reaction was carried out in a standard assay mixture containing 50% (vol/vol) H 2 18 O. The protein concentration was determined according to the method of Bradford, with bovine serum albumin as a standard (3).…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that the reaction involves an unstable intermediate, formed by the initial loss of phosphate, which may be of a radical nature [10], but a cationic mechanism cannot yet be ruled out.…”
mentioning
confidence: 99%